Production process model based on lean manufacturing, TPM and SLP to increase the service level in companies in the textile sector - Ono Yamanija, Andrea (2025)
The textile sector is highly competitive, so quality and efficiency are essential to improve the level of service of companies. For this reason, the implementation of a production model based on Lean Manufacturing, Total Productive Maintenance (TPM) and Simplified Logistics Planning (SLP) becomes a proposal for improvement for the optimization of companies' production processes. This paper will examine in detail the application of this improvement proposal through a case study and the impact that these models have on the efficiency, quality, and ability of the company to know customer demand.